Top Answer

Sum = 69Count = 10

So mean = sum/count = 69/10 = 6.9

Sum = 69Count = 10

So mean = sum/count = 69/10 = 6.9

Sum = 69Count = 10

So mean = sum/count = 69/10 = 6.9

Sum = 69Count = 10

So mean = sum/count = 69/10 = 6.9

🙏

0🤨

0😮

0😂

0Loading...

(11/12) * (2/3) = 0.6111111111111111... or (11/12) * (2/3) = (11*2)/(12*3) = 22/36 = 11/18

2 3/4 / 3 = 11/12 2 3/4 becomes 11/4 3 becomes 12/4 11/4 / 12/4 = 11/12 So you're left with 11/12

11/12 = 91.67% 2/3 = 66.66% 11/12 is bigger

11/12-3/4= 11/12 and 3/4 have different denominators. So we multiply 4 by 3 to get the denominators the same. If we multiply 4 by 3, we should also multiply 3 by 3. 11/12-9/12=2/12 If it asks us it in the simplest form, 2/12 find the LCM, 2. And divide it by 2, 2/12=1/6.

lcm(4, 8, 11, 12) = 264 4 = 2^2 8 = 2^3 11 = 11 12 = 2^2 x 3 lcm = 2^3 x 3 x 11 = 264

If you mean: 12, 11, 9, 6, 2 then the next number is -3 Because they are being reduced by 1, 2, 3, 4 and then 5

12 - (1/6 + 2/3) = 12 - (1/6 + 4/6) = 12 - 5/6 = 11 1/6 or did you mean: 1/6 + (12 - 2/3) = 1/6 + 11 1/3 = 11 + (1/6 + 1/3) = 11 + (1/6 + 2/6) = 11 + 3/6 = 11 + ½ = 11½

(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12

11.6667

For the values: 12, 11, 3, 2 the LCM is: 132

If you mean 3 and 1/4 minus 2 and 1/3 then it is 11/12

660LCM of 10, 11 & 12 = 660Prime factorization of:10 = 2 * 511 = ...........1112 = 2.............* 2 * 3===============LCM=2 * 5 * 11 * 2 * 3 = 660

6.44

11/12 + 3/4 = 11/12 + 9/12 = 20/12 = 5/3 = 1 2/3

1/4 = 3/12 11/12 - 3/12 = 8/12 = 2/3

If you mean 2/3 of 12 then it is 8

factoring 22=2*11 12=2*2*3 6=2*3 9=3*3 lcm=2*2*3*3*11=396

2

2/3 + 1/4 = 8/12 + 3/12 = 11/12

33 = 3 * 1112 = 3 * 2 * 2So: 3.

The mean is the sum of the values divided by the number of values. In this case (12+10+19+8+2+15+1+20+6+11+3+7)/12 = 9.5.

The sum of 11/12 and 2/3 = 1 7/12

1/4 + 2/3 = 3/12 + 8/12 = 11/12

22/24 or 33/36 they are the same, factor and see 2*11/2*12 or 3*11/3*12 eliminate the 2's, top and bottom and the 3,s, top and bottom 11/12 = 11/12

If you mean: 2(a+3)-12 then it can be simplified to 2a-6